Hubungan Dukungan Keluarga dengan Self Care Management Pada Penderita Hipertensi di Wilayah Kerja UPTD Puskesmas Sukawati I - Antari, Luh Putu Juni; Kamaryati, Ni Putu; Krisnandari D, Anak Agung Istri Wulan (Universitas Malahayati, 2024)
ABSTRACT Implementing self care management for patient with hypertension is one way to prevent uncontrolled hypertension. Successful implementation of self care management requires support from family. Good family support will influence the implementation of self care management in hypertensive patients. This stdu aims to determine the correlation between family support and self care management in hypertensive patients in UPTD Puskesmas Sukawati I. This study employed correlation analytical design with cross sectional approach. There were 166 respondents recruited as the sample through convenience sampling technique. Data was collected using questionnaires of family support and Self Care Management and analyzed by using Spearman's Rho in the SPSS version 20. The findings showed there were 67 respondents (40.4%) stated that the family support provided was in sufficient category and 126 respondents (75.9%) were in the category of good self care management. Moreover, there was a significantly associated between family support and self care management (r = 0,804, p-value = < 0,001). Based on the result of the study, it can be concluded that the better family support, the better the application of self care management in hypertensive patients. It is hoped that nurses and community officers can include the families in the hypertension control program. Keywords: Hypertension, Family Support, Self Care Management ABSTRAK Penerapan self care management pada penderita hipertensi salah satu cara mencegah hipertensi yang tidak terkontrol. Dalam keberhasilan penerapan self care management diperlukan dukungan keluarga. Dukungan keluarga yang baik akan berpengaruh terhadap penerapan self care management pada penderita hipertensi. Penelitian ini bertujuan untuk mengetahui hubungan dukungan keluarga dengan self care management pada penderita hipertensi di Wilayah Kerja UPTD Puskesmas Sukawati I. Desain yang digunakan dalam penelitian ini adalah analitik korelasional dengan pendekatan cross sectional. Sampel yang digunakan berjumlah 166 responden dengan teknik convenience sampling. Pengumpulan data menggunakan kuesioner dukungan keluarga dan Self Care Management serrta analisis yang digunakan adalah Spearman’s Rho menggunakan SPSS versi 20. Hasil penelitian ini menunjukkan sebanyak 67 (40.4%) responden menyatakan dukungan keluarga yang diberikan cukup. Sebanyak 126 (75.9%) responden sudah dalam kategori self care management baik. Terdapat hubungan natara dukungan keluarga dengan self care management (r = 0,804, p-value = < 0,001). Semakin baik dukungan keluarga maka semakin baik pula penerapan self care management pada penderita hipertensi. Diharapkan perawat dan petugas ditatanan komunitas dapat mengikutsertakan keluarga dalam program pengendalian hipertensi. Kata Kunci: Hipertensi, Dukungan Keluarga, Self Care Management